1991
DOI: 10.1029/91jd01362
|View full text |Cite
|
Sign up to set email alerts
|

Irreversible transport in the stratosphere by internal waves of short vertical wavelength

Abstract: The U‐2 aircraft was instrumented and flown in the stratosphere during the Stratosphere‐Troposphere Exchange Project's experiments of April 1984 to provide a set of simultaneous measurements by fast responding sensors that would aid in the identification of the modes of cross‐jet transport. The measurements confirm the preexperimental deductions that transport is dominated by waves, not by large‐scale circulations. Monotonic gradients of trace constituents normal to the jet axis, with upper stratospheric trace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(41 citation statements)
references
References 19 publications
2
38
1
Order By: Relevance
“…For the origin of laminae, they suggested that a mechanism operates at the lower edge of the polar vortex (where ozone mixing ratio increases sharply on isentropic surfaces) which transports ozone to middle latitude in the form of laminae, particularly during spring when the polar vortex dissipates. Possible candidates for this mechanism are inertia-gravity waves associated with the subtropical jet stream as proposed by Danielsen et al (1991) or distortions of the polar vortex boundary by synoptic scale motions as proposed by Tuck et al (1992). Reid et al (1994), using the EASOE ozonesonde archive, analyzed the occurrence of laminae in the course of the 1992 winter confirming the findings of Reid and Vaughan (1991) and Reid and Vaughan (1993).…”
Section: Introductionsupporting
confidence: 52%
“…For the origin of laminae, they suggested that a mechanism operates at the lower edge of the polar vortex (where ozone mixing ratio increases sharply on isentropic surfaces) which transports ozone to middle latitude in the form of laminae, particularly during spring when the polar vortex dissipates. Possible candidates for this mechanism are inertia-gravity waves associated with the subtropical jet stream as proposed by Danielsen et al (1991) or distortions of the polar vortex boundary by synoptic scale motions as proposed by Tuck et al (1992). Reid et al (1994), using the EASOE ozonesonde archive, analyzed the occurrence of laminae in the course of the 1992 winter confirming the findings of Reid and Vaughan (1991) and Reid and Vaughan (1993).…”
Section: Introductionsupporting
confidence: 52%
“…Studies using data obtained from ozonesonde ascents show that these laminae are most often encountered during the winter and spring, and that the frequency of ozone laminae tends to increase from subtropical to polar latitudes [Dobson, 1973]. Attempts to understand the processes which give rise to these laminae have focused on the statistical relationship between the frequency of larninae and seasonal changes in the stratospheric circulation [Reid and Vaughan, 1991 herea/•er RV91] and analysis of individual soundings for signatures of wave induced transport [Danielsen et al, 1991]. Quasi-horizontal, meridional transport by planetary and synoptic scale Rossby waves, and vertical transport by gravity waves, are believed to be the primary mechanisms by which the ozone laminae form.…”
Section: Introductionmentioning
confidence: 99%
“…Irreversible mixing is promoted by turbulence induced, for example, by nonlinear wave interaction, wave breaking, or dissipation Whiteway et al, 2003;Koch et al, 2005;Lane and Sharman, 2006). Danielsen et al (1991) showed that waves with large horizontal wavelengths (∼ 36-270 km) and enhanced vertical amplitudes are significant carriers of energy, momentum and trace species. Small-scale waves (horizontal wavelength smaller than 30 km) may cause mixing and thus enable the irreversibility of the transport induced by large-scale waves.…”
Section: R Heller Et Al: Mountain Waves Modulate the Water Vapor DImentioning
confidence: 99%
“…There are a few studies that refer to trace gas transport induced by gravity waves (e.g., Danielsen et al, 1991;Langford et al, 1996;Schilling et al, 1999;Moustaoui et al, 2010). Gravity waves are known to play an important role in the circulation, structure and variability of the atmosphere (Fritts and Alexander, 2003).…”
Section: Introductionmentioning
confidence: 99%